Stylistic Analysis of E.E. Cummings "she being Brand" - Gomez, Johannah; Manayon, Kelly Reign; Batal, Deebee Lyca; Serato, Floramel; Minoza, Joemar (JEE (Journal of English Education), 2024)
The study delves into the stylistic deviations present in E.E. Cummings’ poem "She Being Brand," a work known for intentional phonetic style, creative spelling, and unique syntax. Stylistics, a linguistic branch, provides a systematic approach to comprehend literature by scrutinizing linguistic choices, especially crucial in understanding modern and postmodern literature’s deviations from regular language patterns. The paper’s objectives are to identify and analyze linguistic deviations in the poem, focusing on graphological, lexical, grammatical, and semantic aspects. Additionally, it aims to describe, analyze, and interpret linguistic parallelism, such as anaphora, asyndeton, and epiphora, unveiling their contribution to the poem’s meaning. The study concludes with an original poem inspired by Cummings’ work, showcasing an understanding and admiration for his distinctive style. The comprehensive methodology integrates qualitative analysis to explore the diverse stylistic choices within "She Being Brand." The poem serves as a genuine source reflecting Cummings’ intentional and inventive language during the transformative literary era of modernism. Results and discussions reveal graphological deviations through capitalization, decapitalization, punctuation, and hyphenation, contributing to thematic depth and aesthetic appeal. Lexical deviations include compelling word combinations intensifying emotional depth. Grammatical deviations, like errors and enjambment, disrupt conventional structures, emphasizing the speaker’s emotional state. Semantic deviations, including oxymoron, paradox, and metaphor, introduce layers of meaning. Linguistic parallelism, employing anaphora and asyndeton, enhances rhythmic flow and vividly portrays the speaker’s interaction with the new car. The study concludes that Cummings’ deliberate deviations enrich "She Being Brand," establishing him as a noteworthy contemporary poet. Keywords: Deviations, Grammatically, Graphological, Semantical, Parallelism